Macs, home automation and you. - Berebstain, Adam.
Modernize your home and simplify your life with these painless and strategies that automate your house, apartment, castle, or whatever keeps the roof over your head.
Keywords: Home automation; Home electronics; Electronic surveillance; Streaming audio; Streaming video